A KONTROL OPTIMAL PADA MODEL DINAMIK PENYEBARAN VIRUS KOMPUTER DENGAN MENGGUNAKAN PONTRYAGIN MAXIMUM PRINCIPLE (PMP) - ASMIANTO, ASMIANTO; PUSADWIJAYANTI, KRIDHA; HAFIIZH, MOCHAMMAD (E-Jurnal Matematika, 2020)
In this paper, it is discussed about giving control variable to dynamic systems to process the spread of viruses on computers. The dynamic model describes the process of spreading viruses on the computer, where susceptible can be instantly removed and infected can instantly become susceptible. And through qualitative analysis on the model is given a control and completed using the Pontryagin Maximum Principle (PMP) method on infected interactions so that the infected computer can be minimized. Dynamic models that have been given control are simulated using MATLAB software and the results show the infected computer is reduced enough significan.